Safety of thoracoscopic surgery for lung cancer without interruption of anti-platelet agents - Yu, Woo Sik; Jung, Hee Suk; Lee, Jin Gu; Kim, Dae Joon; Chung, Kyung Young; Lee, Chang Young (Journal of Thoracic Disease, 2015)
Background: Perioperative bleeding concerns have led to the general recommendation that antiplatelet agents (APAs) be discontinued 7-10 days preoperatively, but this could increase the risk of perioperative cardiovascular events. This retrospective study aimed to evaluate the safety of APA continuation during thoracoscopic surgery for lung cancer. Methods: Between January 2009 and February 2015, 164 patients taking APAs underwent curative resection. Comparisons were conducted between two groups: preoperatively interrupted APA administration (group I, n=106) and continued APA administration (group N, n=58). Results: Group N had a significantly higher revised cardiac risk index (rCRI) (P=0.001). Lobectomy was performed in the majority of patients [95 (89.6%) in group I; 52 (89.7%) in group N]. There were no significant differences in intraoperative outcomes, such as the thoracotomy conversion rate, operating time, intraoperative transfusion, and amount of blood loss during the operation, or postoperative outcomes, such as postoperative bleeding and thrombotic complications, postoperative transfusions, and operative mortality. Within group N, the patients taking aspirin + clopidogrel (n=11) had significantly greater postoperative bleeding (P=0.005), and more postoperative transfusions (P=0.003) and chest tube drainage over a 3-day period (P=0.049) compared with other antiplatelet regimens. Conclusions: Continued use of APAs during thoracoscopic surgery for lung cancer could be safely done in patients at high risk of cardiac or thrombotic events. However, in patients administered aspirin + clopidogrel, it may be the best to continue aspirin only because of an increased risk of postoperative bleeding and transfusion requirements.